Light-induced spatial separation of charges toward different crystal facets of square-like WO3. Issue 80 (19th September 2016) - Gong, Huihua; Ma, Ruirui; Mao, Fang; Liu, Kewei; Cao, Hongmei; Yan, Hongjian
Abstract : Light-induced preferential migration of electrons and holes to the minor (200) and (020) facets and the dominant (002) facets of square-like WO3, respectively, resulted in the square-like WO3 nanoplates with Pt loaded mainly on dominant (002) facets shows higher photocatalytic activity than that Pt loaded on the minor facets. Abstract : Light-induced preferential migration of electrons and holes to the minor (200) and (020) facets and the dominant (002) facets of square-like WO3, respectively, resulted in the square-like WO3 nanoplates with Pt loaded mainly on dominant (002) facets shows higher photocatalytic activity than that Pt loaded on the minor facets.